Acorn – weevil interactions in a mixed-oak forest: Outcomes for larval growth and plant recruitment - Muñoz, Alberto; Bonal, Raul; Espelta, Josep Maria (Forest Ecology and Management, 2014)
Weevils are the most important pre-dispersal acorn predators in the Mediterranean region, where oaks often form mixed forests and different weevil species can coexist. The performance of weevil larvae depends in great extent on their feeding activities inside the infested acorns that, in turn, are known to reduce the viability of acorns. In this paper, we have analysed the interactions among the weevil community and four oak species (Quercus pyrenaica, Quercus suber, Quercus faginea and Quercus ilex) coexisting in a Mediterranean mixed-oak forest. DNA sequencing of weevil larvae revealed four different weevil species (Curculio elephas, Curculio glandium, Curculio pellitus and Curculio venosus) infesting the acorns of the four oak species. Oak species differed in acorn size, and weevil species also differed in body size. Weevil species showed some degree of specificity among the four oak species, but specificity was not related to variations in acorn size. By contrast, larval development and seedling recruitment were mostly driven by inter-specific differences in larval and acorn size. Larger seeded species suffered less seed damages by weevils (i.e. embryo predation and cotyledon consumption), thus reducing the impacts of acorn infestation in seedling emergence and seedling size. Larval development for the largest weevil species C. elephas was constrained by cotyledon depletion in all acorn species. Yet, this pattern was not observed for other weevil species. Larval size of the same weevil species also varied among different oak species after controlling for the amount of cotyledon eaten by larvae, thus, variation of other acorn traits among acorn species (e.g. chemical composition) may also have consequences for the performance of weevil larvae. It is likely that other variables operating at population level, such as temporal and spatial changes in acorn production or phenological variations of weevils and oaks, are also implicated in the complex functioning of these outstanding mixed-oak forests where natural regeneration seems to be threatened.
Keywords: acorn; Host specificity; Larval development; Seedling recruitment; Weevil

Seeding phenology influences wood mouse seed choices: the overlooked role of timing in the foraging decisions by seed-dispersing rodents - Sunyer, Pau; Espelta, Josep Maria; Bonal, Raul; Muñoz, Alberto (Behavioral Ecology and Sociobiology, 2014)
Scatter-hoarding rodents influence the population dynamics of plants by acting as seed predators and dispersers. Therefore, rodent foraging preferences for certain seed traits (species, size, condition) have been extensively studied. However, to what extent these preferences are fixed or they track the temporal changes on seed characteristics due to phenological differences has been seldom explored.We stud- ied the temporal variability in seed preferences by wood mouse (Apodemus sylvaticus), according to phenological changes in seed characteristics of two co-occurring oaks (Quercus ilex and Quercus pubescens). The phenology of acorn abundance and the acorn predation/dispersal patterns by rodents were monitored over an entire seeding season. Results revealed temporal changes in rodent preferences for acorns of the two oaks, matching their different seeding phe- nology (earlier in Q. pubescens and later in Q. ilex). On the other hand, whatever the species considered, rodents preferred larger and sound acorns along the entire season, although the dispersal of infested ones increased slightly during the peaks of acorn drop. The observed influence of seeding phenology on seed choices by rodents warns about inferring definite conclusions regarding their foraging behavior when arising from short-term experiments. Indeed, this study reveals that foraging preferences may be highly dynamic and context- dependent for some seed traits (e.g., species and condition), rather than fixed behavioral patterns. Plasticity in rodent for- aging choices may allowthem to successfully exploit different oaks with uncoupled seeding phenologies, while potentially favoring their coexistence.
Keywords: acorn; Apodemus sylvaticus; dispersal; Quercus; seed; seed traits

Growth and survival of cork oak (Quercus suber) seedlings after simulated partial cotyledon consumption under different soil nutrient contents - Mancilla-Leytón, JuanManuel; Cambrollé, Jesús; Figueroa, ManuelEnrique; Martín Vicente, Ángel (Plant and Soil, 2013)
We examined the importance of partial seed consumption (cotyledon loss) by rabbits in the early establishment of seedlings of cork oaks restricted to nutrient-impoverished soils. To determine the importance of cotyledons in the growth and development of seedlings, we simulated two levels of predation [light (30 % cotyledon loss) and heavy (60 % loss) partial consumption] and two soil nutrient contents (nutrient-poor soil, nutrient-rich soil). Seedlings height, root length, dry root and shoot biomass, specific leaf mass, leaf density, gas exchange, chlorophyll fluorescence parameters and photosynthetic pigment concentrations were determined. Results indicated that effect of nutrient level on the growth of the oak seedlings was more important than that of cotyledon biomass. However, in nutrient-poor soils, cotyledon biomass played a major role in the early performance of cork oaks. Acorns grown in nutrient-rich substrate, despite having greater aerial vigor, were slower to develop a vertical root, and hence less likely to reach permanent moisture. Cotyledon loss caused a decrease in the biomass of roots and shoots when acorns were heavily consumed, and as a result experienced a reduction in net photosynthetic rate, stomatal conductance and chlorophyll concentration. Survival of seedlings was unaffected by either soil type or cotyledon loss. Our results show that effects of soil type on the survival of oak seedlings were more important than those of cotyledon biomass. However, in a competitive situation, cotyledon biomass, as an indicative of growth nutrient support rather than an energy source, could be vital in a nutrient-poor environment, particularly in Mediterranean climate regions and for species with little inherent drought tolerance (as is the case of Quercus spp.), where rapid root growth is required to ensure that contact with soil moisture is maintained over the first summer.
Keywords: acorn; Cotyledon loss; Doñana Natural Park; Nutrient; photosynthesis; Predation; seedling establishment

Responses of a scatter-hoarding rodent to seed morphology: links between seed choices and seed variability - Muñoz, Alberto; Bonal, Raul; Espelta, Josep Maria (Animal Behaviour, 2012)
Seed preferences of scatter-hoarding granivores may inﬂuence the evolution of seed traits in plants. However, there is little evidence linking the granivores’ responses to speciﬁc seed traits to the variability of seeds in a single plant species. This information is essential for understanding how the decisions of granivores can shape plant life histories. We analysed how seed morphology (size and shape) of the Holm oak, Quercus ilex, inﬂuences seed choices of the seed-disperser, the Algerian mouse, Mus spretus. We studied the seed variability of the oak and whether the frequency of seed phenotypes matched the seed choices of the disperser. The probabilities of seed removal decreased as the seeds became larger and more bullet-shaped, so that seeds that were simultaneously large and bullet-shaped had the lowest probabilities of being dispersed. These seeds are probably refused by rodents because they impose higher handling and transport costs. The size and shape of the Holm oak seeds were highly variable between trees, but extraordinarily consistent within a single tree over different years. However, the analysis of seed variability revealed a disproportionately low frequency of large bullet-shaped phenotypes, which are those barely removed by rodents. Seed preferences of dispersers of species with high seed variability between trees can lead to differences in the chances of seeds produced by different trees being dispersed. Those seed phenotypes preferred by dispersers could make a higher contribution to the next generation, which could inﬂuence the evolution and variability of seeds in a plant species
Keywords: acorn; Algerian mouse; animal-plant interaction; handling cost; hoarding behaviour; Holm oak; Mus spretus; Quercus ilex; seed caching; small rodent

Starch isolation from chestnut and acorn flours through alkaline and enzymatic methods - Correia, Paula Reis; Beirão-da-Costa, Maria Luísa (Food and Bioproducts Processing, 2012)
Two different procedures were used to isolate chestnut (Castanea sativa Mill.) and acorn (Quercus suber) starch. Starch was extracted from the ﬂour of these dried fruits by: (i) low shear at alkaline pH and successively using three sieves (A3S) at different centrifugation conditions (velocity and time) and (ii) enzymatic treatment at low shear (ENZ) at a different amount/digestion time of protease. In both cases a Central Composite Rotatable Design (CCRD) was used as an experimental design. Results were treated through the Response Surface Methodology (RSM). Based on maximum yield values and the degree of purity, the best modiﬁed conditions encountered were applied in a new trial and mass balance was established for both isolation procedures. The best centrifugation conditions encountered for the A3S isolation method were 800 × g during 15min, and for the ENZ method 900 units of protease despite the incubation time, for the same centrifugation terms. The yields reached with these experimental conditions for the A3S and ENZ methods were 83.9% and 79.9% for chestnut and 88.5% and 86.9% for acorn, respectively. Isolated starches shown to be higher in purity, presented values of 98.3% and 96.3% for chestnut and 98.1% and 97.6% for acorn, respectively for the A3S and ENZ methods
The following values have no corresponding Zotero field: publisher: Institution of Chemical Engineers
Keywords: acorn; chestnut; composition; isolation method; starch; yield

Acorns (Quercus rotundifolia Lam.) and grass as natural sources of antioxidants and fatty acids in the “montanera” feeding of Iberian pig: Intra- and inter-annual variations - Tejerina, D.; García-Torres, S.; Cabeza de Vaca, M.; Vázquez, F. M.; Cava, R. (Food Chemistry, 2011)
In two consecutive years (2006/2007 and 2007/2008), fortnightly samples were taken to characterise the antioxidant composition and fatty acid proﬁle of acorns and grass on which Iberian pigs feed during the period of ‘‘montanera” (free-range rearing system of the south-western of Iberian Peninsula). The antioxidant parameters analysed were: a- and c-tocopherol, total phenolics compounds (TPC), lipophilic and hydrophilic antioxidant activities (LAA, HAA) (acorn and grass) and condensed and hydrolysable tannins (CT, HT) and protein precipitating capacity (PP) (acorns). To characterise the fatty acid proﬁles, the thirteen major fatty acids were assayed. For the acorns, it was found that there was intra-annual variability in all the antioxidants studied except a-tocopherol, and inter-annual variability in all except the protein precipitating capacity. The fatty acid proﬁle also varied depending on the sampling date and the study year, especially in the saturated fatty acids (SFA) and C18:1 n-9 content. For the grass, there was intraand inter-annual variability in all the antioxidant parameters studied, and in the proportions of the fatty acids C18:0, and C18:1. It could explain variations in the antioxidant and fatty acids composition of Iberian pig tissues from animals raised in different ‘‘montanera” seasons and even in the same ‘‘montanera” season.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: acorn; antioxidant; fatty acid; Grass; iberian pig; ‘‘Montanera”

Average daily weight gain of Iberian fattening pigs when grazing natural resources - Rodríguez-Estévez, Vicente; Sánchez-Rodríguez, Manuel; García, Antón R.; Gómez-Castro, a Gustavo (Livestock Science, 2011)
In spite of the growing interest in organic farming and sustainable production, there is a lack of information about the performance of pigs when they feed only on natural resources. This research studied the fattening pattern during the montanera (free-range grazing on acorns and grass during autumn and winter, without any supplementary feed or mineral complement) of the Iberian pig in the dehesa (Quercus ilex open woodlands) in order to know the average daily gain (ADG) and to analyze the inﬂuence of three factors: year of montanera, age and sex of pigs. The fattening data were obtained from two ﬂocks of castrated pigs during the ﬁrst two months (from November the ﬁrst) of two consecutive montaneras (2003 and 2004) on the same farm. Pigs (from 111.8± 0.9 kg BW at introduction) were individually weighed every 15 days in the early morning, with no food intake since the previous evening. The ADG for all pigs was 0.76± 0.01 kg/day; however, some variations were observed according to the year (0.74±0.02 kg/day in 2003 vs. 0.78±0.02 kg/day in 2004; pb0.05), the sex (0.78±0.02 kg/day for males vs. 0.72± 0.02 kg/day for females; pb0.01) and the age (0.71±0.02 kg/day for pigs younger than a year vs. 0.83±0.02 kg/day for pigs older than a year; pb0.001); however a factorial 3-way ANOVA does not show signiﬁcant interaction between factors. Comparing the fortnights periods, the lowest ADG was measured in the ﬁrst 15 days of montanera (0.60±0.02 kg/day), and the highest ADG occurred in the second one (0.85±0.02 kg/day). Later on, the datasets were adjusted with the GLM procedure for the fixed effects of the year of the montanera, the age and the sex. With the adjusted datasets, different regression models for the fattening in montanera were established; the best adjusted of those was the potential model (Y= 0.32*X 1.22 ; X= days of montanera; and Y= kg life weight gained during the montanera). According with this model pigs would need an average of 58 d to fatten 46 kg, as the Iberian Breed Quality Standards demand. Finally, the results show that the age and sex, as factors that inﬂuence the ADG, should be taken into close account to choose pigs and that it is possible to reach a high ADG grazing only with natural resources, following appropriate management strategies such as rationing in order to obtain the beneﬁts of compensatory growth.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: acorn; Compensatory growth; Extensive farming; Free ranging; Grass; Organic farming; Sustainable production

Shrub encroachment in Mediterranean silvopastoral systems: Retama sphaerocarpa and Cistus ladanifer induce contrasting effects on pasture and Quercus ilex production - Rivest, David; Rolo, Víctor; López-Díaz, Lurdes; Moreno, Gerardo (Agriculture, Ecosystems & Environment, 2011)
Silvopastoral systems are threatened worldwide by progressive loss of either tree cover or herbaceous cover due to lack of tree regeneration and shrub encroachment, respectively. Grazed Mediterranean open woodlands, as Iberian dehesa, are an outstanding example of silvopastoral system where shrub encroachment has been proposed as an effective means to facilitate tree seedling recruitment and ensure the system persistence. Shrubs also may interact with pasture understorey and tree overstorey, thereby affecting the overall system productivity. We tested the effects of shrub encroachment on pasture yield, tree growth and acorn production in years of contrasting rainfall in Quercus ilex L. dehesas of centralwestern Spain.We compared the effects oftwo prominentMediterranean shrub species that differ in their ecological strategies: a N2-ﬁxing and sparse deep-rooting shrub (Retama sphaerocarpa (L.) Boiss), and a dense shallow-rooting shrub (Cistus ladanifer L). In intermediate and dry years, pasture yield beneath tree canopy was lower by 21–35% than in open grassland. Pasture yield beneath tree canopy was not signiﬁcantly affected during the wet year. C. ladanifer encroachment signiﬁcantly reduced pasture yield by 68–98%, tree growth by 17–29%, and acorn yield by 6–44%. In contrast, R. sphaerocarpa signiﬁcantly increased pasture yield by 11–157% and tree growth by 6–13%, but had a neutral effect on acorn yield. Our results suggest that pasture is more sensitive to shrub encroachment and annual rainfall variation than is Q. ilex. The importance of C. ladanifer competition and R. sphaerocarpa facilitation on pasture yield increased in the driest year. We conclude that the sign and intensity of shrub encroachment effects on pasture and tree production in Mediterranean dehesas are species-speciﬁc and depend on temporal variation as a function of climate.
Keywords: acorn; Agroforestry; competition; Dehesa; Facilitation; Overstorey–understorey interactions

Chestnut and acorn starch properties affected by isolation methods - Correia, Paula Reis; Beirão-da-Costa, Maria Luísa (Starch - Stärke, 2010)
Starches from chestnut (Castanea sativa Mill.) and acorns (Quercus suber Lam. and Q. rotundifolia Lam.) were isolated from dried fruits using four different methods. These involved a physicochemical and/or an enzymatic treatment followed by centrifugation and sieving: (i) low shear at alkaline pH – LSA, (ii) high shear in water – HSW, (iii) enzymatic treatment at low shear – LSE, (iv) LSA and using successively three sieves – LSA3S. Raw yield, purity, colour parameters, morphology, protein, fat, ash, reducing sugars and amylose contents, damaged starch content and viscoamylographic proﬁles were studied in isolated starches, presenting different properties through different methods. In general, chestnut starch seems to be poorly resistant to extraction methodologies as shown by the damaged starch content and viscoamylographic properties encountered during this study. Moreover, acorn starches exhibited cross-linked amylographic patterns. For all the tested raw materials, the LSA3S isolation method always higher yield and purity of starches. Gelatinization temperature and peak consistency were also higher than those shown by starches produced by the other methods, a less damaged structure was also evident. In conclusion, it seems that this method is the most suitable to produce starch for food ingredient usage.
Keywords: acorn; chestnut; morphology; physicochemical properties; starch isolation methods

An increase in canopy cover leads to masting in Quercus ilex - Camarero, J. Julio; Albuixech, Jorge; López-Lozano, Raúl; Casterad, M. Auxiliadora; Montserrat-Martí, Gabriel (Trees, 2010)
Masting is the intermittent and synchronous production of large crops, but its relation to tree growth remains elusive despite the ecological relevance of mast seeding. The production of huge fruit crops has been linked to the accumulation and consumption of resources as nutrients and carbohydrates, but no conclusive assessment has supported this assumption. To evaluate if masting takes place once trees’ canopies reach maximum foliage, changes in canopy cover were measured in Quercus ilex susbp. ballota stands before and after a masting event using the normalized difference vegetation index (NDVI). The results on the whole underline that masting in Q. ilex occurred once maximum levels of NDVI and canopy cover were reached. After the masting event, NDVI dropped, leaf shedding increased and trees produced shorter shoots, narrower tree rings and fewer acorns than before the masting event. These ﬁndings support our contention that an increase in canopy cover precedes masting.
Keywords: acorn; canopy cover; Mast seeding; quercus ilex subsp. ballota; Remote sensing

Mismatch between the timing of oviposition and the seasonal optimum. The stochastic phenology of Mediterranean acorn weevils - Bonal, Raul; Muñoz, Alberto; MARÍA ESPELTA, JOSEP (Ecological Entomology, 2010)
1. The timing of reproduction is predicted to match the period of maximum food availability. In this sense, the case of many phytophagous insects in temperate regions is very illustrative, as their larvae usually depend on a resource only available for a limited period of time each year. 2. For 3 years the interactions between the weevil Curculio elephas and the Mediterranean Holm oak Quercus ilex were studied. Weevil larvae grow within the acorns, feeding on the cotyledons. The timing of oviposition will determine food availability for the larvae, as acorns stop growing once they are attacked. 3. Acorn temporal growing patterns did not change between years and food availability for larvae was at its highest in October, when temperature was still suitable for larval development. However, oviposition phenology did change between years. In 2002 females oviposited later, larvae grew within larger acorns, and their body mass was significantly higher than in 2003 or 2004, when females oviposited into early acorns. 4. Thus, weevils do not always adjust oviposition to the best possible feeding conditions for their offspring. Rather, they seem to maximise their own lifetime fitness, ovipositing as soon as they emerge in late summer. Emergence, in turn, depends strongly on stochastic events such as summer storms in the Mediterranean region. 5. Under a climate change perspective, the trend towards higher August rainfall recorded in our study area may alter oviposition phenology, with the subsequent cascade effects on weevil body size and fitness
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: acorn; adult emergence; Curculio; oviposition; Phenology; stochastic events; Temperature; timing of reproduction

On sweet acorn (Quercus spp.) cake tradition in Italian cultural and ethnic islands - Pignone, Domenico; Laghetti, Gaetano (Genetic Resources and Crop Evolution, 2010)
The CNR-IGV, over the last 15 years, has organized and performed expeditions aimed at collecting germplasm and local knowledge on plants used by local populations in isolated areas, such as geographical islands, or local communities that for ethnic or cultural reasons have maintained to a certain degree their isolation from surrounding populations (cultural islands). In two such cultural islands (Bovesia, Calabria region, south-west mainland Italy, and Ogliastra, Sardinia island, Italy) a tradition regarding the use of acorns for preparing a cake was recorded. In Ogliastra, an elder lady still retains the knowledge regarding the collections, maintenance and utilization of acorns for preparing a cake, a knowledge once common and now quite completely disappeared. The present paper reports on the culture associated to acorn used as a food for humans.
Keywords: acorn; Cultural islands; Ethnobotany; Neglected food; Quercus spp.

Seed weevils living on the edge: pressures and conflicts over body size in the endoparasitic Curculio larvae - Bonal, Raul; Muñoz, Alberto (Ecological Entomology, 2009)
Abstract 1. Body size in parasitic insects can be subjected to contrasting selective pressures, especially if they complete their development within a single host. On the one hand, a larger body size is associated with a higher fitness. On the other hand, the host offers a discrete amount of resources, thus constraining the evolution of a disproportionate body size. 2. The present study used the weevil Curculio elephas as a study model. Larvae develop within a single acorn, feeding on its cotyledons, and larval body size is strongly related to individual fitness. 3. The relationship between larval and acorn size was negatively exponential. Larval growth was constrained in small acorns, which did not provide enough food for the weevils to attain their potential size. Larval size increased and levelled off in acorns over a certain size (inflexion point), in which cotyledons were rarely depleted. When there were more than one larva per acorn, a larger acorn was necessary to avoid food depletion. 4. The results show that C. elephas larvae are sometimes endoparasitic, living on the edge of host holding capacity. If they were smaller they could avoid food depletion more easily, but the fitness benefits linked to a larger size have probably promoted body size increase. The strong negative effects of conspecific competition may have possibly influenced female strategy of laying a single egg per seed. 5. Being larger and fitter, but always within the limits of the available host sizes, may be one main evolutionary dilemma in endoparasites.
Keywords: acorn; Body size; Curculio; endoparasitism; food constraints; granivorous insects; Holm oak; host size; larvae

Seed weevils living on the edge: pressures and conflicts over body size in the endoparasitic Curculio larvae - Bonal, Raul; Muñoz, Alberto (Ecological Entomology, 2009)
Abstract 1. Body size in parasitic insects can be subjected to contrasting selective pressures, especially if they complete their development within a single host. On the one hand, a larger body size is associated with a higher fitness. On the other hand, the host offers a discrete amount of resources, thus constraining the evolution of a disproportionate body size. 2. The present study used the weevil Curculio elephas as a study model. Larvae develop within a single acorn, feeding on its cotyledons, and larval body size is strongly related to individual fitness. 3. The relationship between larval and acorn size was negatively exponential. Larval growth was constrained in small acorns, which did not provide enough food for the weevils to attain their potential size. Larval size increased and levelled off in acorns over a certain size (inflexion point), in which cotyledons were rarely depleted. When there were more than one larva per acorn, a larger acorn was necessary to avoid food depletion. 4. The results show that C. elephas larvae are sometimes endoparasitic, living on the edge of host holding capacity. If they were smaller they could avoid food depletion more easily, but the fitness benefits linked to a larger size have probably promoted body size increase. The strong negative effects of conspecific competition may have possibly influenced female strategy of laying a single egg per seed. 5. Being larger and fitter, but always within the limits of the available host sizes, may be one main evolutionary dilemma in endoparasites.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: acorn; Body size; Curculio; endoparasitism; food constraints; granivorous insects; Holm oak; host size; larvae

Acorn production in Spanish holm oak woodlands - Gea-Izquierdo, G.; Cañellas, I.; Montero, G. (Forest Systems, 2008)
We present a review on the state-of-the-art of fruit prodution in Western Iberia woodlands («dehesas»), and particularly in Q. ilex (holm oak) «dehesas». This threatened ecosystem is of very high ecological and economical importance. Quercus sp. fruits (acorns) are essential for wildlife, and for pig fattening in «dehesas». In the first part of this review we briefly describe the phenology of the holm oak and the factors affecting acorn morphology and chemical composition. In the second half we analyze the main known factors reported in the literature that determine acorn production: pruning, stand characteristics, and site (weather and soil). We make several suggestions to improve future research and detect the existing gaps in the undertanding of acorn production. Fruit production is highly variable, both between and within years and individuals. The mean production in «dehesas» (mean density circa 50 trees/ha) is around 250-600 kg/ha (≈100 g/canopy-m2 , CV> 100%). Acorn morphology is also very variable, with mean sound acorn size around 3.5 × 1.6 cm, CV ≈ 10% (3.5 g/acorn, CV > 50%). Silviculture plays an essential role in acorn production. Acorn production per tree seems to be negatively related to density. The effect of pruning is less clear: production seems to be reduced in the first and second years after pruning. After the third year it is not possible to discern from the literature whether there is any response to pruning or not. Weather and soil (site) also impact production and their effects should be explored in future management. The influence of genetics is unknown and should also be addressed. Longer data series are necessary. The dasometric features of the stands need to be characterized, in order to better understand production and compare results from different locations. Much research is still required to understand the functioning of fruiting in these woodlands.
Keywords: acorn; agrosilvopastoral systems; Dehesa; fruit production; Holm oak; Quercus ilex

Acorn production in Spanish holm oak woodlands - Gea-Izquierdo, G; Cañellas, I; Montero, G (Forest Systems, 2008)
We present a review on the state-of-the-art of fruit prodution in Western Iberia woodlands («dehesas»), and particularly in Q. ilex (holm oak) «dehesas». This threatened ecosystem is of very high ecological and economical importance. Quercus sp. fruits (acorns) are essential for wildlife, and for pig fattening in «dehesas». In the first part of this review we briefly describe the phenology of the holm oak and the factors affecting acorn morphology and chemical composition. In the second half we analyze the main known factors reported in the literature that determine acorn production: pruning, stand characteristics, and site (weather and soil). We make several suggestions to improve future research and detect the existing gaps in the undertanding of acorn production. Fruit production is highly variable, both between and within years and individuals. The mean production in «dehesas» (mean density circa 50 trees/ha) is around 250-600 kg/ha (≈100 g/canopy-m2 , CV> 100%). Acorn morphology is also very variable, with mean sound acorn size around 3.5 × 1.6 cm, CV ≈ 10% (3.5 g/acorn, CV > 50%). Silviculture plays an essential role in acorn production. Acorn production per tree seems to be negatively related to density. The effect of pruning is less clear: production seems to be reduced in the first and second years after pruning. After the third year it is not possible to discern from the literature whether there is any response to pruning or not. Weather and soil (site) also impact production and their effects should be explored in future management. The influence of genetics is unknown and should also be addressed. Longer data series are necessary. The dasometric features of the stands need to be characterized, in order to better understand production and compare results from different locations. Much research is still required to understand the functioning of fruiting in these woodlands.
Keywords: acorn; agrosilvopastoral systems; Dehesa; fruit production; Holm oak; Quercus ilex

Cork oak (Quercus suber L.) acorn as a substitute for barley in the diet of rabbits; Effect on In vivo digestibility, growth and carcass characteristics. J. anim - Boubaker, A. Gasmi; Abduli, H.; Lozada, M. R. M. (Journal of Animal and Veterinary Advances, 2007)
In this study 2 experiments were conducted to evaluate the feeding value of cork oak acorn as an energy source for rabbits. Experiment 1 was a digestibility trial using 20 adult rabbits (10 rabbits/group) and experiment 2 was a growth performance and carcass evaluation using 24 growing rabbits in a completely randomised design. Two diets were formulated to contain either 250 g Dry Matter (DM) barley (Barley diet) or 250 g DM oak Acorn (Acorn diet)/kg and included mainly, wheat bran, soybean meal, hay, molasses, calcium phosphate, Cu SO4 and salt. Inclusion of acorn in the diet did not result in any change in odour and fungal contamination nor in the feed intake (p>0.05). However, acorn in the diet decreased the in vivo digestibility by 10.8, 11.5 and 17.5%, respectively, for DM, Organic Matter (OM) and Crude Protein (CP). Although the rabbits fed acorn diet retained less nitrogen than those fed barley diet, they were positive in the nitrogen balance. The final live weight and daily weight gain from weaning through slaughter did not show any significant difference between rabbits fed the control diet and those fed the experimental diet. Similar carcass yield and feed conversion ratio were observed for the 2 groups. Weight of full gastrointestinal, liver, kidney and caecum were not affected (p>0.05) by the presence of acorn in the experimental diet. A more careful evaluation of the real content and digestibility of nutrients from acorn is necessary to evaluate their nutritional value before considering them as a potential feed for rabbits.
Keywords: acorn; digestibility; Growth; rabbit; tannin

Cork oak (Quercus suber L.) acorn as a substitute for barley in the diet of rabbits; Effect on In vivo digestibility, growth and carcass characteristics. J. anim - Boubaker, A Gasmi; Abduli, H; Lozada, M R M (Journal of Animal and Veterinary Advances, 2007)
In this study 2 experiments were conducted to evaluate the feeding value of cork oak acorn as an energy source for rabbits. Experiment 1 was a digestibility trial using 20 adult rabbits (10 rabbits/group) and experiment 2 was a growth performance and carcass evaluation using 24 growing rabbits in a completely randomised design. Two diets were formulated to contain either 250 g Dry Matter (DM) barley (Barley diet) or 250 g DM oak Acorn (Acorn diet)/kg and included mainly, wheat bran, soybean meal, hay, molasses, calcium phosphate, Cu SO4 and salt. Inclusion of acorn in the diet did not result in any change in odour and fungal contamination nor in the feed intake (p>0.05). However, acorn in the diet decreased the in vivo digestibility by 10.8, 11.5 and 17.5%, respectively, for DM, Organic Matter (OM) and Crude Protein (CP). Although the rabbits fed acorn diet retained less nitrogen than those fed barley diet, they were positive in the nitrogen balance. The final live weight and daily weight gain from weaning through slaughter did not show any significant difference between rabbits fed the control diet and those fed the experimental diet. Similar carcass yield and feed conversion ratio were observed for the 2 groups. Weight of full gastrointestinal, liver, kidney and caecum were not affected (p>0.05) by the presence of acorn in the experimental diet. A more careful evaluation of the real content and digestibility of nutrients from acorn is necessary to evaluate their nutritional value before considering them as a potential feed for rabbits.
Keywords: acorn; digestibility; Growth; rabbit; tannin

Influence of pollen emission and weather-related factors on variations in holm-oak (Quercus ilex subsp. ballota) acorn production - García-Mozo, H.; Gómez-Casero, M. T. T.; Dominguez, E.; Galan, C. (Environmental and Experimental Botany, 2007)
In Iberian Mediterranean ecosystems holm-oak acorn production is of vital ecological and economic importance. Economically these fruits are the major component in the feeding systems of high-quality domestic pigs. As in most Quercus species, the chief feature of holm-oak acorn production is its high variability among individuals and years. Many hypotheses have been put forward to explain these ﬂuctuations, but the variables inﬂuencing this alternating behavior remain unknown. From 1998 to 2003 we studied ﬂoral phenology, fruit production, fruit size, airborne pollen emission and meteorology in a holm-oak natural area of South Spain. The results obtained by using a Principal Components Factorial Analysis indicated that pollen emission, up to the day where maximum pollen data are recorded, was the most important factor determining ﬁnal acorn harvest. With regard to the inﬂuence of the weather, temperature, relative humidity and rainfall of January, March and September were the most inﬂuencing variables. Our results support the “wind pollination” hypothesis proposed by other authors in some North-American Quercus studies. Integration of aerobiological, ﬁeld phenological and meteorological data could represent an important step forward in forest fruit production research.
Keywords: acorn; Aerobiology; ballota; holm-oak; oak forest; Phenology; pollen; quercus ilex subsp; quercus ilex subsp. ballota

Influence of pollen emission and weather-related factors on variations in holm-oak (Quercus ilex subsp. ballota) acorn production - García-Mozo, H.; Gómez-Casero, M.T. T; Dominguez, E.; Galan, C. (Environmental and Experimental Botany, 2007)
In Iberian Mediterranean ecosystems holm-oak acorn production is of vital ecological and economic importance. Economically these fruits are the major component in the feeding systems of high-quality domestic pigs. As in most Quercus species, the chief feature of holm-oak acorn production is its high variability among individuals and years. Many hypotheses have been put forward to explain these ﬂuctuations, but the variables inﬂuencing this alternating behavior remain unknown. From 1998 to 2003 we studied ﬂoral phenology, fruit production, fruit size, airborne pollen emission and meteorology in a holm-oak natural area of South Spain. The results obtained by using a Principal Components Factorial Analysis indicated that pollen emission, up to the day where maximum pollen data are recorded, was the most important factor determining ﬁnal acorn harvest. With regard to the inﬂuence of the weather, temperature, relative humidity and rainfall of January, March and September were the most inﬂuencing variables. Our results support the “wind pollination” hypothesis proposed by other authors in some North-American Quercus studies. Integration of aerobiological, ﬁeld phenological and meteorological data could represent an important step forward in forest fruit production research.
Keywords: acorn; Aerobiology; ballota; holm-oak; oak forest; Phenology; pollen; quercus ilex subsp; quercus ilex subsp. ballota

Pattern recognition of acorns from different Quercus species based on oil content and fatty acid profile - Ferreira-Dias, Suzana; Valente, Dina G.; Abreu, José M.F. F (Grasas y Aceites, 2007)
The aim of this study was (i) to characterize different species of Quercus genus and (ii) to discriminate among them on the basis of the content and fatty acid composition of the oil in their fruits and/or their morphological aspects via pattern recognition techniques (Principal Component Analysis, PCA, Cluster Analysis, CA, and Discriminant Analysis, DA). Quercus rotundifolia Lam., Quercus suber L. and Quercus pyrenaica Willd., grown in the same stand in the centre of Portugal, were investigated. When oil content and respective fatty acid composition were used to characterize samples, well-separated groups corresponding to each of the species were observed by PCA and confirmed by CA and DA. The ‘‘width’’ and ‘‘length’’ of acorns exhibited a low discriminant power. Acorns from Q. rotundifolia showed the highest average oil content followed by Q. suber and Q. pyrenaica acorns (9.1, 5.2 and 3.8%, respectively). Fatty acid profiles of Q. rotundifolia and Q. suber oils are similar to olive oil while the oil from Q. pyrenaica acorns is more unsaturated
Keywords: acorn; cluster analysis; Discriminant analysis; Oil; Principal component analysis; Quercus

Pattern recognition of acorns from different Quercus species based on oil content and fatty acid profile - Ferreira-Dias, Suzana; Valente, Dina G.; Abreu, José M. F. F. (Grasas y Aceites, 2007)
The aim of this study was (i) to characterize different species of Quercus genus and (ii) to discriminate among them on the basis of the content and fatty acid composition of the oil in their fruits and/or their morphological aspects via pattern recognition techniques (Principal Component Analysis, PCA, Cluster Analysis, CA, and Discriminant Analysis, DA). Quercus rotundifolia Lam., Quercus suber L. and Quercus pyrenaica Willd., grown in the same stand in the centre of Portugal, were investigated. When oil content and respective fatty acid composition were used to characterize samples, well-separated groups corresponding to each of the species were observed by PCA and confirmed by CA and DA. The ‘‘width’’ and ‘‘length’’ of acorns exhibited a low discriminant power. Acorns from Q. rotundifolia showed the highest average oil content followed by Q. suber and Q. pyrenaica acorns (9.1, 5.2 and 3.8%, respectively). Fatty acid profiles of Q. rotundifolia and Q. suber oils are similar to olive oil while the oil from Q. pyrenaica acorns is more unsaturated
Keywords: acorn; cluster analysis; Discriminant analysis; Oil; Principal component analysis; Quercus

Supercritical carbon dioxide extraction of acorn oil - Bernardo-Gil, M Gabriela; Lopes, Isabel M G; Casquilho, Miguel; Ribeiro, M Albertina; Esquível, M Mercedes; Empis, José (The Journal of Supercritical Fluids, 2007)
Acorn fruit oil of Quercus rotundifolia L. (holm-oak) was extracted with compressed carbon dioxide in the temperature range of 35–60 ◦ C and in the pressure range of 12–21 MPa. The inﬂuences of particle size, CO2 density, solvent ﬂow rate, and extractor geometry were studied. Two different tubular extractors were used: extractor 1 of 0.2 L of capacity, internal diameter D = 45.7 mm, height/diameter ratio H/D = 1.5, and extractor 2 of 0.09 L of capacity, internal diameter D = 21.3 mm, and H /D = 12. It was found that the yield and the initial extraction rate depend on the carbon dioxide density and superﬁcial velocity, and on the ratio of bed height to D, at the same conditions of temperature, pressure, and particle size. In the beginning of extraction, CO2 density is the preponderant factor, but after some time of extraction, the fraction of oil directly exposed to the solvent, which is dependent on particle size, becomes the most important factor. The Sovova model was successfully applied to the description of the supercritical extraction curves of acorn oil
Keywords: acorn; Extraction; Quercus rotundifolia L.; Sovová model; Supercritical carbon dioxide

Supercritical carbon dioxide extraction of acorn oil - Bernardo-Gil, M. Gabriela; Lopes, Isabel M. G.; Casquilho, Miguel; Ribeiro, M. Albertina; Esquível, M. Mercedes; Empis, José (The Journal of Supercritical Fluids, 2007)
Acorn fruit oil of Quercus rotundifolia L. (holm-oak) was extracted with compressed carbon dioxide in the temperature range of 35–60 ◦ C and in the pressure range of 12–21 MPa. The inﬂuences of particle size, CO2 density, solvent ﬂow rate, and extractor geometry were studied. Two different tubular extractors were used: extractor 1 of 0.2 L of capacity, internal diameter D = 45.7 mm, height/diameter ratio H/D = 1.5, and extractor 2 of 0.09 L of capacity, internal diameter D = 21.3 mm, and H /D = 12. It was found that the yield and the initial extraction rate depend on the carbon dioxide density and superﬁcial velocity, and on the ratio of bed height to D, at the same conditions of temperature, pressure, and particle size. In the beginning of extraction, CO2 density is the preponderant factor, but after some time of extraction, the fraction of oil directly exposed to the solvent, which is dependent on particle size, becomes the most important factor. The Sovova model was successfully applied to the description of the supercritical extraction curves of acorn oil
Keywords: acorn; Extraction; Quercus rotundifolia L.; Sovová model; Supercritical carbon dioxide

Fruit abortion, developmental selection and developmental stability in Quercus ilex. - Díaz, Mario; Møller, Anders P.; Pulido, Fernando J. (Oecologia, 2003)
Fruit abortion has been hypothesized to be a parental means of selective removal of propagules with low viability. In particular, aborted zygotes have been suggested to have developmentally deviant phenotypes, and surviving offspring may therefore give rise to adults with a developmentally stable phenotype. We tested predictions from this hypothesis using acorns of holm oaks Quercus ilex as a model system. Fecundity of oak trees was negatively related to mean fluctuating asymmetry of leaves, and abortion rates were positively related to leaf fluctuating asymmetry in at least one population. Aborted acorns were asymmetric in 83-99% of cases in three samples, while mature acorns were only asymmetric in 57-78% of cases. Acorn asymmetry was unrelated to germination probability and germination date, and had no significant effect on number of leaves, leaf mass, stem mass, seedling height or leaf area of seedlings. However, acorn asymmetry affected the trade-off between number and size of leaves in seedlings. Seedlings from asymmetric acorns showed a positive relationship between acorn size and number of leaves, but no relationships between acorn size and leaf area, while symmetric acorns showed the opposite. A positive relationship between acorn size and number of leaves in spring was found for naturally emerged seedlings that died during their first summer, whereas the number of leaves produced by surviving seedlings did not depend on acorn size. These findings are consistent with the hypothesis that stressed trees selectively abort propagules of low viability, and that developmental selection acts on a measure of developmental instability of fruits.
The following values have no corresponding Zotero field: accession-num: 12721827
Keywords: acorn; Fluctuating asymmetry; Leaf number; Leaf size; Maternal effect

Fruit abortion, developmental selection and developmental stability in Quercus ilex. - Díaz, Mario; Møller, Anders P; Pulido, Fernando J (Oecologia, 2003)
Fruit abortion has been hypothesized to be a parental means of selective removal of propagules with low viability. In particular, aborted zygotes have been suggested to have developmentally deviant phenotypes, and surviving offspring may therefore give rise to adults with a developmentally stable phenotype. We tested predictions from this hypothesis using acorns of holm oaks Quercus ilex as a model system. Fecundity of oak trees was negatively related to mean fluctuating asymmetry of leaves, and abortion rates were positively related to leaf fluctuating asymmetry in at least one population. Aborted acorns were asymmetric in 83-99% of cases in three samples, while mature acorns were only asymmetric in 57-78% of cases. Acorn asymmetry was unrelated to germination probability and germination date, and had no significant effect on number of leaves, leaf mass, stem mass, seedling height or leaf area of seedlings. However, acorn asymmetry affected the trade-off between number and size of leaves in seedlings. Seedlings from asymmetric acorns showed a positive relationship between acorn size and number of leaves, but no relationships between acorn size and leaf area, while symmetric acorns showed the opposite. A positive relationship between acorn size and number of leaves in spring was found for naturally emerged seedlings that died during their first summer, whereas the number of leaves produced by surviving seedlings did not depend on acorn size. These findings are consistent with the hypothesis that stressed trees selectively abort propagules of low viability, and that developmental selection acts on a measure of developmental instability of fruits.
Keywords: acorn; Fluctuating asymmetry; Leaf number; Leaf size; Maternal effect

Amino acid availability and energy value of acorn in the Iberian pig - Aguilera, J. F.; Nieto, R.; Rivera, M.; Garcıa, M. A. (Livestock Production Science, 2002)
Two experiments have been performed to determine amino acid digestibility and energy value of acorn (Quercus rotundifolia L.) for Iberian pigs. In experiment 1 ileal digestibility of amino acids was determined in ﬁve ileum-cannulated growing pigs fed whole ground acorn. An estimation of endogenous protein losses was carried out by feeding a protein-free diet, added (180 g/kg) or not with acorn hulls. True ileal digestibility of all essential amino acids measured was high (0.798–1.03) except for arginine (0.523), lysine (0.601), isoleucine (0.760), leucine (0.777) and phenylalanine (0.716). The average value for the digestibility of the sum of amino acids was 0.664. Lysine was the ﬁrst limiting amino acid compared with the amino acid proﬁle of the ideal protein for pigs. In experiment 2, total tract digestibility of nutrients and N balance were determined in ﬁve, non-cannulated pigs offered whole acorns. High coefﬁcients for the apparent total tract digestibility of dry matter (ApDM) (0.830) and energy metabolizability (ME/GE; 0.805) were found. ME content for acorn kernel was 16.6 MJ/kg DM, while the apparent total tract digestibility of total N (ApTN) was as low as 0.408. However, a positive N retention was observed (3.7 g/day). Comparing experiments 1 vs. 2, inclusion of acorn hulls resulted in a marked decrease in DM intake, ApTN and in N retention (25.1 g/day, in total tract data from experiment 1). The negative effects of acorn hulls on protein digestibility and N balance were corroborated in rats given similar amounts of either whole ground acorn or ground acorn kernel. Dietary supplementation with lysine is proposed to achieve a higher efﬁciency of protein accretion in the Iberian pig when fed on acorn.
Keywords: acorn; amino acids; energy value; pig-feeding and nutrition; protein quality

Amino acid availability and energy value of acorn in the Iberian pig - Aguilera, J F; Nieto, R; Rivera, M; García, M A (Livestock Production Science, 2002)
Two experiments have been performed to determine amino acid digestibility and energy value of acorn (Quercus rotundifolia L.) for Iberian pigs. In experiment 1 ileal digestibility of amino acids was determined in ﬁve ileum-cannulated growing pigs fed whole ground acorn. An estimation of endogenous protein losses was carried out by feeding a protein-free diet, added (180 g/kg) or not with acorn hulls. True ileal digestibility of all essential amino acids measured was high (0.798–1.03) except for arginine (0.523), lysine (0.601), isoleucine (0.760), leucine (0.777) and phenylalanine (0.716). The average value for the digestibility of the sum of amino acids was 0.664. Lysine was the ﬁrst limiting amino acid compared with the amino acid proﬁle of the ideal protein for pigs. In experiment 2, total tract digestibility of nutrients and N balance were determined in ﬁve, non-cannulated pigs offered whole acorns. High coefﬁcients for the apparent total tract digestibility of dry matter (ApDM) (0.830) and energy metabolizability (ME/GE; 0.805) were found. ME content for acorn kernel was 16.6 MJ/kg DM, while the apparent total tract digestibility of total N (ApTN) was as low as 0.408. However, a positive N retention was observed (3.7 g/day). Comparing experiments 1 vs. 2, inclusion of acorn hulls resulted in a marked decrease in DM intake, ApTN and in N retention (25.1 g/day, in total tract data from experiment 1). The negative effects of acorn hulls on protein digestibility and N balance were corroborated in rats given similar amounts of either whole ground acorn or ground acorn kernel. Dietary supplementation with lysine is proposed to achieve a higher efﬁciency of protein accretion in the Iberian pig when fed on acorn.
Keywords: acorn; amino acids; energy value; pig-feeding and nutrition; protein quality

PRODUCCION DE BELLOTA EN QUERCUS ROTUNDIFQLIA LAM.: VARIABILIDAD ANUAL E IMPORTANCIA ECONOMICA - Esparrago, F; Vázquez, F M; Burzaco, A; Perez, M C (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
The acorn production on Q. rotundifolia Lam. has been analyzed from 1989 through 1992 in Extremadura. The efects of different areas, each tree, and the interaction between areas/years are significatives. Genetic, pruning, environment and phytosanitary factors are the possible causes of these differences. Finally, the econornic efects of acorn production on iberian pig feeding (Montanera) has been studied. This is the rnain factor for high quality products.
Keywords: acorn; Econorny; evergreen oak; feeding; iberian pig; production; Quercus

PRODUCCION DE BELLOTA EN QUERCUS ROTUNDIFQLIA LAM.: VARIABILIDAD ANUAL E IMPORTANCIA ECONOMICA - Esparrago, F.; Vázquez, F. M.; Burzaco, A.; Perez, M. C. (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
The acorn production on Q. rotundifolia Lam. has been analyzed from 1989 through 1992 in Extremadura. The efects of different areas, each tree, and the interaction between areas/years are significatives. Genetic, pruning, environment and phytosanitary factors are the possible causes of these differences. Finally, the econornic efects of acorn production on iberian pig feeding (Montanera) has been studied. This is the rnain factor for high quality products.
The following values have no corresponding Zotero field: periodical: Congreso Forestal Español, Lourizán - Pontevedra. 1993
Keywords: acorn; Econorny; evergreen oak; feeding; iberian pig; production; Quercus